Determination of the virulence and antifungal susceptibilities of oral Candiba albicans isolates from patients undergoing cancer treatment - Ramla, Shilpa (My University, 2013)
Chemotherapy and radiation therapy are fundamental treatments for malignancies. Due to these cancer therapies, patients have a greater predisposition towards mucositis and oral candidiasis. Oral candidiasis is caused by Candida species. Not much is known about the effect that cancer treatments have on the virulence determinant and antimicrobial sensitivity of C. albicans isolated from the oral cavities of cancer patients. The aim of this study was to investigate the effect of cancer treatment on the virulence and antifungal sensitivities of C. albicans isolated from the oral cavities of cancer patients undergoing radiotherapy and chemotherapy in a South African tertiary hospital.
A research report submitted to the faculty of Health Sciences, School of Oral Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science of Dentistry, 2013.
Keywords: Candida albicans